MODEL OF HOSPITAL SERVICE COMMUNICATION IN MULTI-ETNICAL COMMUNITIES IN RSUD Dr. H. SOEMARNO SOSROATMODJO KUALA KAPUAS - Popo Subroto; Muzahid Akbar Hayat; Khuzaini Khuzaini; Sanusi Sanusi (SEAN Institute, 2022)
The hospital service communication model has a role in supporting the success of health services. A good and effective communication model in health services to patients in a hospital is the main thing in maintaining the quality and image of an institution that is engaged in health services. Application of appropriate communication model in multiethnic society in RSUD dr. H. Soemarno Sosroatmodjo Kuala Kapuas has a challenge in terms of the use of various regional languages ​​according to the ethnicity of the patient. This is what makes it unique in the implementation of the communication model for hospital services in multiethnic communities at RSUD dr. H. Soemarno Sosroatmodjo Kuala Kapuas. The purpose of this study was to determine the Communication Model for Hospital Services in Multiethnic Communities in RSUD dr. H. Soemarno Sosroatmodjo Kuala Kapuas. The research method used is a qualitative research method with a phenomenological study approach. Data collection techniques using observation techniques, interviews, and documentation. The results obtained from the research found that the communication model for hospital services in multiethnic communities in RSUD dr. H. Soemarno Sosroatmodjo Kuala Kapuas is using King's Interaction Communication Model.